A carbon-supported catalyst and its preparation method and application

By loading metal oxides on carbon support materials, carbon-supported catalysts are prepared, which solves the problems of complex operation and high cost of traditional deoxygenation catalysts, and achieves efficient and low-cost olefin conversion, which has good sustainability and industrial applications. value.

CN116651432BActive Publication Date: 2025-02-07HUAQIAO UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310590769.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-24
Publication Date
2025-02-07
Estimated Expiration
2043-05-24

AI Technical Summary

Technical Problem

Traditional deoxygenation catalysts have the disadvantages of complex operation, high cost, and low selectivity of olefins, making it difficult to effectively utilize renewable resources to convert them into olefins.

Method used

Using a carbon-supported catalyst, a highly efficient deoxygenation catalyst is prepared by supporting metal oxides on a carbon support material and loading by ultrasonic method. This method uses solid waste from the petrochemical industry as carbon carriers to achieve resource utilization.

Benefits of technology

It realizes low-cost and efficient conversion of olefins from oils and fatty acids, and the selectivity of olefins can reach 66%, while reducing the dependence on high pressure and hydrogen, and has good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116651432B_ABST
    Figure CN116651432B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of olefin production by deoxidation catalyst, and in particular to a carbon-supported catalyst and its preparation method and application. The preparation method of the carbon-supported catalyst comprises the following steps: obtaining a metal-containing carbonaceous material, grinding it into a powder, stirring and soaking it with an acidic solution at 30-80°C, separating and drying it to obtain a carbon carrier material; using water as a reaction solvent, adding a soluble transition metal salt, an organic ligand, a surfactant and an alkaline substance to react, and obtaining a precursor material, wherein the organic ligand is 3,5-pyridinedicarboxylic acid; washing and roasting the obtained precursor material to obtain an oxide material; using an ultrasonic method to load the obtained oxide material on the carbon carrier material to obtain a carbon-supported catalyst. The method provided by the present invention overcomes the shortcomings of complex operation, high cost, and low olefin selectivity in traditional deoxidation catalysts, and has certain market application value and advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparing olefins using a deoxygenation catalyst, and in particular to a carbon-supported catalyst and a preparation method and application thereof. Background Art

[0002] With the rapid development of the world's industrial economy, the demand for olefins at home and abroad is increasing. Olefins are important chemical raw materials extracted from fossil resources, mainly from the oligomerization of ethylene, and are widely used in petrochemicals, light industry, textiles, metallurgy, medicine, pesticides, etc. At present, due to the global warming and fossil resource depletion, the popularization of alternative energy and the development of renewable fuels and important chemicals are gradually increasing. Among them, the conversion of biomass to prepare olefins has received extensive attention.

[0003] The production process starting from renewable resources is very important for sustainable development. Biomass energy, as the fourth largest energy source after coal, oil and natural gas, occupies an important position. Deoxygenation of oils and fats is an important way to prepare hydrocarbon energy, mainly including direct hydrodeoxygenation, in-situ hydrodeoxygenation and decarboxylation and decarbonylation. Among them, the oxygen atoms of oils and fats are converted to CO during the decarboxylation process. 2 In the decarbonylation process, the oxygen atoms of oils and fats are converted to CO and H 2 O is removed to produce olefins. Since the decarboxylation and decarbonylation pathway does not require high pressure, hydrogen supply, and the participation of hydrogen supply reagents, it is more in line with the concept of green development and has been widely studied in recent years. At present, traditional deoxygenation catalysts have the disadvantages of relying on precious metal materials, complex operation, high cost, unstable surface properties, and easy deactivation. Therefore, the carbon-supported deoxygenation catalyst prepared by using chemically treated waste residue as a carbon carrier material to load metal oxides has good application prospects for the conversion of renewable resources into olefins. At the same time, the petroleum waste residues produced by the non-catalytic partial oxidation process in the petrochemical industry can also be used as resources, which has important environmental significance and potential economic benefits. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and to provide a carbon-supported catalyst and a preparation method and application thereof.

[0005] In order to solve the above technical problems, the technical solutions provided by the present invention are as follows:

[0006] A method for preparing a carbon-supported catalyst comprises the following steps:

[0007] Obtaining metal-containing carbonaceous materials, grinding them into powder, stirring and soaking them in an acidic solution at 30-80° C., separating and drying them to obtain a carbon carrier material;

[0008] Using water as a reaction solvent, adding a soluble transition metal salt, an organic ligand, a surfactant and an alkaline substance to react, thereby preparing a precursor material, wherein the organic ligand is 3,5-pyridinedicarboxylic acid;

[0009] The obtained precursor material is cleaned and calcined to obtain an oxide material;

[0010] The prepared oxide material is loaded on the carbon support material by using an ultrasonic method to obtain a carbon-supported catalyst.

[0011] It should be noted that the metal-containing carbonaceous waste residue can be waste residue produced by a non-catalytic partial oxidation process in the petrochemical industry. The waste residue raw material has the highest metal content of V, followed by Ni and Fe. Therefore, the present invention particularly uses an acidic solution at 30-80° C. for treatment to achieve the best metal elution effect;

[0012] Secondly, the ultrasonic method used in the present invention has the advantage of convenient operation. In the process of ultrasonically mixing the waste residue, oxide material and solvent, the loading method has a better effect, and the utilization rate of the oxide material is extremely high. Most of it can be loaded on the waste residue. The ultrasonic solvent used in the ultrasonic method can be water, ethanol, etc., which has little harm, is not easy to volatilize, and will not cause damage to the environment.

[0013] In a more preferred embodiment, the mass ratio of the oxide material to the carbon carrier material is 0.1-1.6:1. By adopting this ratio, the carbon carrier material can be more fully loaded with the oxide material without causing material waste. At this ratio, the performance after loading is better.

[0014] In a more preferred embodiment, the ratio of the mass of the waste residue to the volume of the acid solution is 1g:15-80mL.

[0015] In a more preferred embodiment, the volume ratio of the total molar amount of the soluble transition metal salt to the aqueous solution is 0.36-3.6 mmol:10-120 mL, the ratio of the total molar amount of the soluble transition metal salt to the molar amount of the organic ligand and the total molar amount of the alkaline substance is 1:1:1, and the added amount of the surfactant is 0.01-0.08 g.

[0016] In a more preferred embodiment, the soluble transition metal salt is at least one of a nickel salt, a zinc salt or a cobalt salt;

[0017] Wherein, the nickel salt is at least one of nickel nitrate, nickel chloride, nickel sulfate and nickel acetate; the zinc salt is at least one of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate; the cobalt salt is at least one of cobalt nitrate, cobalt chloride, cobalt sulfate and cobalt acetate.

[0018] In a more preferred embodiment, the acidic solution is a mixed solution of one or more of hydrochloric acid solution, nitric acid solution, sulfuric acid solution, phosphoric acid solution and phosphorous acid solution, the concentration of the acidic solution is 0.5-2.0 mol / L, and the immersion time is 0.5-12h.

[0019] In a more preferred embodiment, the surfactant is at least one of polyvinyl pyrrolidone, sodium lauryl sulfate, hexadecyl trimethyl ammonium bromide and hexadecyl trimethyl ammonium chloride;

[0020] In a more preferred embodiment, the alkaline substance is one or both of potassium hydroxide and sodium hydroxide.

[0021] In a more preferred embodiment, the reaction time for preparing the precursor material is 6-48 hours.

[0022] In a more preferred embodiment, the ultrasonic time is 0.25-6h.

[0023] The present invention provides a carbon-supported catalyst prepared by the preparation method as described above.

[0024] The present invention provides an application of the carbon-supported catalyst as described above in the deoxygenation reaction of oils and fats and / or fatty acids.

[0025] In a more preferred embodiment, the mass ratio of the oil and / or fatty acid raw material to the carbon-supported catalyst is 0.1-1.0:1-20.

[0026] In summary, the present application includes at least one of the following beneficial technical effects:

[0027] 1. The technical solution of the present invention is adopted to use metal organic framework materials as precursors to calcine metal oxides, and waste carbon is used as a carrier to load the oxides to prepare a deoxygenation catalyst, thereby overcoming the shortcomings of traditional deoxygenation catalysts such as complex operation, high cost, and low olefin selectivity.

[0028] 2. The present invention adopts a thermal cracking-gas chromatography-mass spectrometry device, and the conversion rate of the deoxygenation reaction using coconut oil as the raw material can reach 100%. It does not require pressurization and the participation of hydrogen or hydrogen supply reagents, has low cost and is easy for industrial scale-up production, is harmless to the environment, and the selectivity of olefins can reach 66%. The conversion rate of the deoxygenation reaction of other oils and / or fatty acids can reach more than 85%, and the selectivity of olefins can reach more than 55%.

[0029] 3. The present invention utilizes solid waste from the petrochemical industry as a carbon carrier, realizes resource utilization of solid waste, and has certain market application value and advantages.

[0030] The present invention fully realizes the conversion of renewable green energy, can alleviate the shortage of fossil energy to a certain extent, protect the environment, and play an important role in industrial substitution.

[0031] Other features and beneficial effects of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other beneficial effects of the present invention can be realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. The positional relationships described in the drawings in the following description are based on the directions in which the components are drawn in the diagrams, unless otherwise specified.

[0033] Figure 1 This is a scanning electron microscope (SEM) image of the nickel-zinc composite metal oxide prepared in Example 1 of the present invention; the SEM characterization test adopts a SU-5000 field emission scanning electron microscope, and the acceleration voltage is 8 kV;

[0034] Figure 2 This is a scanning electron microscope (SEM) image of the carbon-supported catalyst prepared in Example 1 of the present invention; the SEM characterization test adopts a SU-5000 field emission scanning electron microscope, and the acceleration voltage is 8 kV;

[0035] Figure 3 This is the X-ray diffractometer spectrum (XRD) of the carbon-supported catalyst prepared in Example 1 of the present invention; the XRD characterization test adopts SmartLab X-ray powder diffractometer. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; the technical features designed in different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0037] In the description of the present invention, it should be noted that all terms used in the present invention (including technical terms and scientific terms) have the same meanings as those generally understood by ordinary technicians in the field to which the present invention belongs, and cannot be understood as limiting the present invention; it should be further understood that the terms used in the present invention should be understood to have the same meanings as these terms in the context of this specification and in the relevant fields, and should not be understood in an idealized or overly formal sense, unless explicitly defined in the present invention.

[0038] The technical solution of the present invention is further illustrated and described below through specific embodiments, but the protection scope of the present invention is not limited thereto.

[0039] Example 1

[0040] (1) obtaining waste residues produced by a non-catalytic partial oxidation process in the petrochemical industry, grinding the waste residues into powder, immersing 1 g of the powdered waste residues in 30 mL of a 0.5 mol / L nitric acid solution at 30° C. for 3 h, performing solid-liquid separation, and drying to remove moisture to obtain a carbon support material;

[0041] (2) At room temperature, 100 mL of water was added as a reaction solvent, 0.45 mmol of nickel chloride and 0.45 mmol of zinc acetate were added, and 0.9 mmol of an organic ligand 3,5-pyridinedicarboxylic acid, 0.02 g of polyvinyl pyrrolidone and 0.9 mmol of sodium hydroxide were added at the same time, and the reaction was aged for 24 hours to obtain a precursor material;

[0042] (3) The material obtained in step (2) was centrifuged at a speed of 12000 rpm for 5 min, and washed three times by centrifugation with water or ethanol solution. The solid was collected and calcined in a muffle furnace at 500° C. for 4 h to obtain an oxide material;

[0043] (4) 10 mg of the oxide material and 50 mg of the carbon support material were mixed, and added to an appropriate amount of aqueous solution, ultrasonicated for 2 h, and dried to obtain the carbon-supported catalyst;

[0044] (5) The carbon-supported catalyst obtained in step (4) is used for the deoxygenation reaction of oils and fats, 0.5 mg of stearic acid is taken as the reaction raw material, the amount of carbon-supported catalyst is 5 mg, the cracking temperature is set to 360°C, and the catalytic deoxygenation temperature is set to 405°C.

[0045] The SEM image of the composite metal oxide prepared in this embodiment is shown in the attached Figure 1 As shown in the figure, it can be seen that the composite metal oxide material prepared by this method is a loose and porous rod-like structure with a length of 2-5μm. The SEM image of the prepared carbon-supported catalyst is shown in the attached Figure 2As shown in the figure, it can be seen that the oxide is loaded on the carbon support. The XRD spectrum of the prepared carbon-supported catalyst is shown in the attached Figure 3 As shown, the successful preparation of the carbon-supported catalyst was proved. Through thermal cracking-gas chromatography-mass spectrometry analysis, it was calculated that the conversion rate of fatty acids reached 99% and the selectivity of olefins reached 63%.

[0046] Example 2

[0047] In step (2) of Example 1, 0.45mmol nickel chloride was adjusted to 0.45mmol nickel nitrate, and 0.45mmol zinc acetate was adjusted to 0.45mmol cobalt nitrate; the aging time of 24h was adjusted to 16h. The remaining process parameters were the same as those of Example 1. The successful preparation of the carbon-supported catalyst was confirmed by SEM analysis and XRD spectra. The conversion rate of fatty acids was calculated to reach 98% and the selectivity of olefins exceeded 59% by thermal cracking-gas chromatography-mass spectrometry analysis.

[0048] Example 3

[0049] In step (2) of Example 1, 0.02 g of polyvinyl pyrrolidone was adjusted to 0.01 g of hexadecyl trimethyl ammonium chloride; in step (3) of Example 1, the calcination conditions of 500° C. and 4 h were adjusted to 650° C. and 2 h; the remaining process parameters were the same as in Example 1. The successful preparation of the carbon-supported catalyst was confirmed by SEM analysis and XRD spectra. The conversion rate of fatty acids was calculated to be 98% and the selectivity of olefins was 56% by thermal cracking-gas chromatography-mass spectrometry analysis.

[0050] Example 4

[0051] In step (2) of Example 1, 0.45mmol nickel chloride was adjusted to 0.56mmol nickel chloride; 0.45mmol zinc acetate was adjusted to 0.56mmol zinc acetate; 0.9mmol organic ligand 3,5-pyridinedicarboxylic acid was adjusted to 1.12mmol; 0.9mmol sodium hydroxide was adjusted to 0.56mmol sodium hydroxide and 0.56mmol potassium hydroxide; in step (4) of Example 1, the mass of 10mg oxide material was adjusted to 20mg, so that the mass ratio of oxide to carbon carrier was 0.5:1; the other process parameters were the same as in Example 1. The successful preparation of the carbon-supported catalyst was proved by SEM analysis and XRD spectrum. By thermal cracking-gas chromatography-mass spectrometry analysis, it was calculated that the conversion rate of fatty acids reached 97% and the selectivity of olefins reached 55%.

[0052] Example 5

[0053] In step (4) of Example 1, the mass of 10 mg of oxide material was adjusted to 5 mg; the ultrasonic time of 2 h was adjusted to 1 h; in step (5) of Example 1, 0.5 mg of stearic acid was adjusted to 0.4 mg of coconut oil; the mass of 5 mg of carbon-supported catalyst was adjusted to 8 mg, so that the mass ratio of oxide to carbon support was 0.625:1; the other process parameters were the same as in Example 1. The successful preparation of the carbon-supported catalyst was confirmed by SEM analysis and XRD spectrum. The conversion rate of oil and fat was calculated to be 94% and the selectivity of olefins was 62% by thermal cracking-gas chromatography-mass spectrometry analysis.

[0054] Example 6

[0055] In step (5) of Example 1, 0.5 mg of stearic acid was adjusted to 0.65 mg of myristic acid; the pyrolysis temperature of 360°C was changed to 285°C; and the other process parameters were the same as those of Example 1. The successful preparation of the carbon-supported catalyst was confirmed by SEM analysis and XRD spectra. The conversion rate of fatty acids was calculated to be 89% and the selectivity of olefins was 57% by thermal pyrolysis-gas chromatography-mass spectrometry analysis.

[0056] Example 7

[0057] In step (2) of Example 1, the volume of 100 mL of reaction solvent water was adjusted to 80 mL; 0.45 mmol of nickel chloride was adjusted to 0.45 mmol of nickel nitrate; in step (5) of Example 1, 0.5 mg of stearic acid was adjusted to 0.1 mg of coconut oil; and the catalytic deoxygenation temperature was adjusted to 420°C. The remaining process parameters were the same as those of Example 1. The successful preparation of the carbon-supported catalyst was confirmed by SEM analysis and XRD spectra. The conversion rate of oil and fat was calculated to be 100% and the selectivity of olefins was 63% by thermal cracking-gas chromatography-mass spectrometry analysis.

[0058] Example 8

[0059] In step (2) of Example 1, 0.45mmol nickel chloride and 0.45mmol zinc acetate are adjusted to 0.9mmol zinc nitrate, which contains only one metal salt; the aging time is adjusted from 24h to 12h; in step (5) of Example 1, 0.5mg stearic acid is adjusted to 0.3mg soybean oil; the amount of carbon-supported catalyst is adjusted to 10mg. The remaining process parameters are the same as those of Example 1. The successful preparation of the carbon-supported catalyst is proved by SEM analysis and XRD spectrum. By thermal cracking-gas chromatography-mass spectrometry analysis, it is calculated that the conversion rate of oil and fat reaches 97%, and the selectivity of olefins reaches 60%.

[0060] Example 9

[0061] In step (2) of Example 1, the volume of 100 mL of reaction solvent water is adjusted to 80 mL; 0.45 mmol of nickel chloride is adjusted to 0.45 mmol of nickel sulfate; in step (5) of Example 1, 0.5 mg of stearic acid is adjusted to a mixture of 0.1 mg of coconut oil and 0.15 mg of stearic acid; the cracking temperature of 360°C is changed to 370°C; the catalytic deoxygenation temperature is adjusted to 430°C. The remaining process parameters are the same as those of Example 1. The successful preparation of the carbon-supported catalyst was demonstrated by SEM analysis and XRD spectra. By thermal cracking-gas chromatography-mass spectrometry analysis, it was calculated that the conversion rate of the oil and fatty acid mixture reached 98%, and the selectivity of olefins reached 57%.

[0062] It should be noted that the specific parameters or some commonly used reagents in the above embodiments are specific embodiments or preferred embodiments of the present invention, rather than limiting them; those skilled in the art can make adaptive adjustments within the scope of the present invention. In addition, unless otherwise specified, the raw materials used can also be conventional commercial products in the art, or prepared by conventional methods in the art.

[0063] Comparative Example 1

[0064] In step (4) of Example 1, no loading experiment was performed to prepare the carbon-supported catalyst; in step (5) of Example 1, the amount of the carbon-supported catalyst was adjusted from 5 mg to 5 mg of the oxide material obtained in step (3). The remaining process parameters were the same as those of Example 1. The conversion rate of fatty acids was calculated to be 42% and the selectivity of olefins was 32% by thermal cracking-gas chromatography-mass spectrometry analysis.

[0065] Comparative Example 2

[0066] In step (4) of Example 1, no loading experiment was performed to prepare the carbon-supported catalyst; in step (5) of Example 1, 0.5 mg of stearic acid was adjusted to 0.5 mg of coconut oil, and the amount of carbon-supported catalyst was adjusted to 5 mg of the oxide material obtained in step (3). The remaining process parameters were the same as those of Example 1. Through thermal cracking-gas chromatography-mass spectrometry analysis, it was calculated that the conversion rate of oil and fat reached 35%, and the selectivity of olefins reached 39%.

[0067] In addition, those skilled in the art should understand that, although there are many problems in the prior art, each embodiment or technical solution of the present invention can be improved in only one or several aspects, without having to solve all the technical problems listed in the prior art or background technology at the same time. Those skilled in the art should understand that the content not mentioned in a claim should not be used as a limitation on the claim.

[0068] Although the terms such as carbon support material, oxide material, precursor material, carbon-supported catalyst, etc. are used more frequently in this article, the possibility of using other terms is not excluded. These terms are used only to more conveniently describe and explain the essence of the present invention; interpreting them as any additional restrictions is contrary to the spirit of the present invention; the terms "first", "second", etc. (if any) in the description and claims of the embodiments of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence.

[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. Use of a carbon-supported catalyst in the deoxygenation reaction of oils and / or fatty acids, characterized in that: The method for preparing the carbon-supported catalyst comprises the following steps: Obtaining metal-containing carbonaceous materials, grinding them into powder, stirring and soaking them in an acidic solution at 30-80° C., separating and drying them to obtain a carbon carrier material; Using water as a reaction solvent, adding a soluble transition metal salt, an organic ligand, a surfactant and an alkaline substance to react, thereby preparing a precursor material, wherein the organic ligand is 3,5-pyridinedicarboxylic acid; The obtained precursor material is cleaned and calcined to obtain an oxide material; The prepared oxide material is loaded on the carbon support material by using an ultrasonic method to obtain the carbon-supported catalyst; Wherein, the soluble transition metal salt is at least one of a nickel salt, a zinc salt or a cobalt salt, the nickel salt is at least one of nickel nitrate, nickel chloride, nickel sulfate and nickel acetate, the zinc salt is at least one of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate, and the cobalt salt is at least one of cobalt nitrate, cobalt chloride, cobalt sulfate and cobalt acetate.

2. The use according to claim 1, characterized in that: The mass ratio of the oxide material to the carbon support material is 0.1-1.6:

1.

3. The use according to claim 1, characterized in that: The ratio of the mass of the powder to the volume of the acidic solution is 1 g:15-80 mL.

4. The use according to claim 1, characterized in that: The volume ratio of the total molar amount of the soluble transition metal salt to the aqueous solution is 0.36-3.6mmol:10-120mL, the ratio of the total molar amount of the soluble transition metal salt to the molar amount of the organic ligand and the total molar amount of the alkaline substance is 1:1:1, and the added amount of the surfactant is 0.01-0.08g.

5. The use according to claim 1, characterized in that: The acidic solution is a mixed solution of one or more of hydrochloric acid solution, nitric acid solution, sulfuric acid solution, phosphoric acid solution and phosphorous acid solution. The concentration of the acidic solution is 0.5-2.0 mol / L, and the soaking time is 0.5-12h.

6. The use according to claim 1, characterized in that: The surfactant is at least one of polyvinyl pyrrolidone, sodium lauryl sulfate, hexadecyl trimethyl ammonium bromide and hexadecyl trimethyl ammonium chloride.

7. The use according to claim 1, characterized in that: The alkaline substance is one or both of potassium hydroxide and sodium hydroxide.

Citation Information

Patent Citations

  • Preparation method of activated carbon loaded metal-nitrogen-carbon catalyst

    CN115025799A